GERMAN INTERNATIONAL COOPERATION DALAM THE URBAN NEXUS PROJECT TERHADAP PEMBANGUNAN PERKOTAAN PEKANBARU 2014-2016 - Safitri Andani; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is about a contemporery issue in international relations study which gives description and analyse about cooperation between pekanbaru cities and GIZ (german international cooperation) on The Urban Nexus Project concerning on urban issues of pekanbaru in 2014 until 2016. GIZ support this program through a Memorandum of understanding (MoU) in cooperation to manage waste water and solid waste implementation pilot project Pekanbaru.This research was develeoped based on he framework of Neo-realism perspectives that is supported by the theory of international cooperation by Kalevi Jaakko Holsti, as well as the level of analysis using the nation-state group. The methods that used in this research is qualitatibe research with data collection obtained from interview, books, journals, articles, internet and other media.The government of Pekanbaru city has commited to implement the cooperation with German international cooperation (GIZ) on The Urban Nexus Project. This project help the government on handling urban issues of Pekanbaru, such in managing solid waste and sanitation (wastewater) the Pekanbaru city.Keywords: Theory of International cooperation, The Urban Nexus Project, nation state group